2011
DOI: 10.1002/app.35416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis and characterization of poly(2,5‐dimethoxy aniline) salts

Abstract: ABSTRACT:The interfacial interaction and orientation of molecules during the polymerization process plays a vital role in the enhancement of the surface properties of conducting polymers. In this perspective, a solid-phase mechanochemical route is employed to prepare poly(2,5-dimethoxy aniline) (PDMA) and its salts with superior properties. Various studies performed on the as-prepared polymer highlights the formation of polymeric particles with excellent physicochemical properties. Elemental analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This can be explained by the effect of the doping acid size; i.e. if the doping acid size is large, the diffusion of doping acid into the polymer matrix will be hindered 48 . On increasing the potential from 1.0 to 1.6 V, the response times of the PDMA films in both acid electrolytes decrease due to the increase of the conductivity upon increasing the applied potential 49 .…”
Section: Response and Reversibility Of Poly(25-dimethoxyaniline) Filmmentioning
confidence: 99%
“…This can be explained by the effect of the doping acid size; i.e. if the doping acid size is large, the diffusion of doping acid into the polymer matrix will be hindered 48 . On increasing the potential from 1.0 to 1.6 V, the response times of the PDMA films in both acid electrolytes decrease due to the increase of the conductivity upon increasing the applied potential 49 .…”
Section: Response and Reversibility Of Poly(25-dimethoxyaniline) Filmmentioning
confidence: 99%
“…The results of the response time of PDMA from various acids indicate that the increase in the polymerization time contributes to the increase in the thickness of the PDMA films and a more compact structure, resulting in slower response time. Moreover, the HCl-PDMA film shows the fastest response time (3⋅7 s) relative to other acids at the same synthesis time, because it produces the thinnest film and the smallest doping acid size resulting in a faster doping process (Palaniappan et al 2012). Furthermore, it is found that the 3⋅7 s response time of the HCl-PDMA is faster than the ITO/PDMA||LiClO 4 -PC-PEO (400,000)|| WO 3 /ITO device (Huang et al 2002), since liquid electrolyte has greater ion mobility than gel electrolyte.…”
Section: 6b Effect Of Testing Potentials On Response Timementioning
confidence: 99%
“…Mechanochemical synthesis (grinding in a mortar with a pestle or ball‐milling) presents viable green routes for the preparation of novel molecular and supramolecular solids . This novel way of synthesis leads directly to products in powder form.…”
Section: Introductionmentioning
confidence: 99%